Comparison of days lost due to disability and Karnofsky performance status in burden of diclofenac induced adverse drug reactions - D, Thomas; M, Mathew; B.J, Mahendra Kumar (Indian Journal of Pharmacy Practice)
Basic objective of this study was to find out the benefit of Days Lost due to Disability (DLD) over Karnofsky Performance Status (KPS) in detecting the burden of Adverse Drug Reactions (ADRs) of diclofenac tablet in clinically recovered male and female groups. This was a cohort study done in 1000 prescriptions of diclofenac tablets to find out the burden of its ADRs in a popular pharmacy in Kasaragod District, Kerala, India. Stratified randomized sampling was done to male and female strata to compare DLD and QoLusing KPS. DLD considers incidence and duration of ADRs in addition to the QoL component, disability weight to give a more complete burden of disease score. For cutaneous reaction, female scored 61 DLD over 26 in male. For peptic ulcer female scored 40 over 37 in male, even though males had higher incidence. Female suffered from higher DLD in other ADRs too. DLD was found to be more complete and sensitive tool than KPS QoL tool in calculating the burden of ADRs due to diclofenac tablet. Female gender is a contributing factor of increased burden of ADRs.
Keywords: peptic ulcer; diclofenac; ADR; female